Analysis of the effectiveness of management by the chief coach of professional volleyball team during competitions - Mozolev, O.; Kovalcuk, R.; Gnydiuk, O.; Tomkiv, I.; Binkovskyi, O.; Melnikov, V.; Tatarin, O. (International Journal of Human Movement and Sports Sciences, 2023)
The article analyzes games of the best volleyball teams in the national championships of Italy, Poland, the Czech Republic and Ukraine. Total number of the games is 46 (n=46). An expert assessment of the content of time-outs (n=571); effectiveness of player substitution (n=1397); use of video replays (n=753) has been provided. The objective is to analyze the content and effectiveness of the management of the chief coach on the tactical actions of professional volleyball team during competitions. Methods include analysis of scientific, methodical, sports sources; monitoring the performance of volleyball teams in national championships, statistical data of competition protocols and video surveillance results; survey; factor analysis of the effectiveness of the team's tactical actions; method of expert assessment, methods of mathematical statistics. The results show that the use of timeouts in professional volleyball has been found to be one of the most effective team management tools. It was determined that 58.1% of the attention of coaches is focused on the specifics of the organization of defensive actions, and 39.4% - on the effective completion of attacking actions. Chief coaches of volleyball teams during time-outs focus the attention of players on the following tactical and technical actions: determining the features of the location of players when receiving complex innings of an opponent; informing the players about the specifics of the organization of defensive actions; organizing the interaction of blocking players. Most often, players are replaced for the simultaneous replacement of connecting and diagonal players in order to change the tactical scheme of the game, for strengthening the innings, it's diversifying, and for strengthening the block on the front line. It concludes that the modern coach of a professional volleyball team is an active participant in the game. It is thanks to the active actions of the chief coach that in 32 sets (17.4%) the players of the professional volleyball team managed to turn the tide of the game in their favor.